Environmental Impacts of Chemical Composition Produced Water - Mammadova, N.I. (Herald of Azerbaijan Engineering Academy, 2024)
This paper examines the effect of produced water from oil and gas production on the environment. Produced water, a complex mixture of different organic and inorganic compounds (mostly salts, minerals, and oils), is a major wastewater generated during oil and gas production. The many chemical components found in formation water, in high enough concentrations, can present a threat to marine life when discharged into sea environments or when discharged to soil ecosystems. Produced water is an inextricable part of the hydrocarbon recovery process and it the important to optimize the management volume of this water. This water must be adequately handled, to prevent and/or minimize environmental degradation. The hydrochemical composition and its impact on the environment is given in the article. Thus, a disposal method was proposed to manage the volume of formation water in production and to increase its efficiency in the re-injected process (on the Siyazan field example).